Pengaruh Kepemimpinan dan Kompetensi Tutor terhadap Prestasi Belajar melalui Motivasi Belajar pada Warga Belajar Pendidikan Kesetaraan di Kota Salatiga - Pamuji, Zaenal Arifin Wahyu; Sutarto, Joko (Didaktika Dwija Indria, 2025)
This study aims to analyze the influence of leadership and tutor competence on learning achievement through learning motivation as a mediating variable among learners of equivalency education in Salatiga City. This research employed a quantitative approach with an associative method. The population consisted of 3,039 equivalency education learners in Salatiga City, while the sample comprised 98 respondents selected using proportional random sampling. Data were collected through questionnaires, limited interviews, and documentation, then analyzed using descriptive statistics, correlation analysis, multiple regression, and Sobel tests with the assistance of SPSS version 26. The findings reveal that leadership and tutor competence have a positive and significant effect on learning motivation. Furthermore, leadership, tutor competence, and learning motivation simultaneously exert a positive and significant influence on learning achievement. Learning motivation also significantly mediates the effect of leadership and tutor competence on learning achievement, with the highest Beta coefficient of 0.400, indicating that learning motivation is the most dominant factor in improving learning outcomes. These results highlight that enhancing the learning achievement of equivalency education learners largely depends on the tutors’ ability to foster learning motivation through effective leadership, professional competence, and contextually relevant instructional strategies.